The Effect Of Service Quality, Company Image And Prices On Customer Loyalty Through Customer Satisfaction On Consumers Using Line Transportation Applications In Students Of The Faculty Of Psychology - Lina Kurniati; Salman Faris; Efendy Pakpahan; Kuras Purba (TRIGIN PUBLISHER, 2022)
his research was conducted to determine the effect of service quality, company image, and price on customer loyalty through customer satisfaction on consumers who use online transportation applications either directly or indirectly. The population in this study were students of the Faculty of Psychology T.A. 2021-2022, the sampling technique uses the accidental sampling technique. The sample used in this study was 84 people, the data collection method used a questionnaire/questionnaire distributed via a google form link and the data analysis method used was path analysis. The results showed that service quality had an insignificant effect on customer loyalty by 0.150, company image had a significant effect on customer loyalty by 0.001, price had an insignificant effect on customer loyalty by 0.077, customer satisfaction had a significant effect on customer loyalty by 0.000, service quality had an insignificant effect. to customer satisfaction is 0.152, company image has no significant effect on customer satisfaction is 0.019, price has no significant effect on customer satisfaction is 0.595, customer satisfaction mediates service quality to customer loyalty is 0.0227, customer satisfaction mediates corporate image to customer loyalty is 1, satisfaction customers mediate price on customer loyalty of 0.652.